A Study on Occupational Stress among Teachers of Higher Educational Institutions in Dharmapuri District, Tamil Nadu, India - Sundareshan, Savitha; Krishnasamy, Krishnakumar (International Review of Management and Marketing, 2024)
This study delves into the issue of occupational stress among teacher educators, aiming to explore its prevalence and associated factors. Through correlation studies, it was observed that a majority of the correlations were both positive and significant. Gender did not emerge as a differentiating factor in occupational stress levels, yet private teacher educators exhibited higher stress levels compared to those in government institutions. The findings underscore the significant role of systemic working conditions and environment in contributing to occupational stress among teacher educators. To mitigate the adverse effects of stress on teacher educators, policymakers, stakeholders, educators, and management must collaborate to implement measures aimed at reducing stress levels, including creating conducive working conditions and providing adequate support systems. This study contributes valuable insights into the understanding of occupational stress among teacher educators and underscores the importance of addressing this issue to promote a healthier and more sustainable teaching profession.